Standardization of proton-induced x-ray emission technique for analysis of thick samples. (10th August 2015) - Ali, Shad; Zeb, Johar; Ahad, Abdul; Ahmad, Ishfaq; Haneef, M.; Akbar, Jehan
Abstract: This paper describes the standardization of the proton-induced x-ray emission (PIXE) technique for finding the elemental composition of thick samples. For the standardization, three different samples of standard reference materials (SRMs) were analyzed using this technique and the data were compared with the already known data of these certified SRMs. These samples were selected in order to cover the maximum range of elements in the periodic table. Each sample was irradiated for three different values of collected beam charges at three different times. A proton beam of 2.57 MeV obtained using 5UDH-II Pelletron accelerator was used for excitation of x-rays from the sample. The acquired experimental data were analyzed using the GUPIXWIN software. The results show that the SRM data and the data obtained using the PIXE technique are in good agreement.